Assessment of knowledge and awareness among dentists about COVID-19 infection: A qualitative study - Priyadeep Banerjee; Shilpi K Pandey; Balaji Sugriv Munde; Godavari Deepak Nagargoje; Sana Mohani; Mitra Ashok Shinde (Wolters Kluwer Medknow Publications, 2021)
Background: This study was an attempt to evaluate the knowledge and awareness among dentists about COVID-19 infection. Methodology: This study was conducted among 580 dental professionals that comprised graduates (BDS), masters (MDS), postgraduates, and PhD fellows. A questionnaire containing information about knowledge, attitude, and awareness about COVID-19 infection was administered and recorded. Results: A total of 493 (85%) respondents replied correct answer that SARS-CoV-2 causes COVID-19. A total of 464 (80%) respondents replied that SARS-CoV-2 is the highest infectious virus among all. A total of 510 (88%) respondents replied the correct answer that 2-14 days is the incubation period of COVID-19 virus. Only 116 (20%) respondents replied the correct answer that MERS has high mortality. Only 87 (15%) respondents were aware of the appropriate mortality rate of COVID-19 disease. A total of 455 (78.4%) respondents had knowledge of the method of detecting COVID-19 infection (real-time reverse transcription-polymerase chain reaction). Knowledge level was good as seen in 81%, fair in 9.5%, and poor in 10.5% of the respondents. Conclusion: The authors found that dental professionals had fair knowledge and awareness regarding COVID-19 infection.